Utilization of soursop leaves as antihyperuricemic in functional beverage ‘Herbal Green Tea’ - Hardoko (2019)
Soursop leaves contain several bioactive compounds which are important for health, including antihyperuricemic activity. Moreover, a processing into green tea could increase their active compounds activity. Therefore, a research was done to determine in vitro antihyperuricemic activity on soursop leaves brew which was processed into herbal green tea. Research method was done by processing soursop leaves according to green tea making procedure and brewed them at 70°C, 85°C and 100°C for 15, 30 and 45 minutes. Antihyperuricemic activity was measured in vitro using xanthine oxidase enzyme and compared to dried soursop leaves brew and fresh soursop leaves brew. Results showed that brewing of herbal green tea from soursop leaves at 100°C for 30 minutes showed the highest inhibition activity towards xanthine oxidase, with IC50 value of 291.11 ± 13.69 ppm. Inhibition activity of herbal green tea was higher than dried soursop leaves brew and fresh soursop leaves brew, which had IC50 value of 648.92±15.34 ppm and 2111.20 ± 55.50 ppm, respectively. Herbal green tea brew from soursop leaves contains total phenolic, flavonoid and condensed tannin content higher than dried soursop leaves and fresh soursop leaves. Physically, herbal green tea brew from soursop leaves has reddish yellow color, similar to original tea brew, but it was not well accepted by panelists due to specific aroma and taste from soursop leaves.